Debating democratization in Myanmar - Cheesman, Nick; Farrelly, Nicholas 1982-; Wilson, Trevor 1943- (Myanmar update series, 2014)
Is Myanmar (Burma) democratizing, or is it moving towards a new form of authoritarianism, perhaps one more consonant with other contemporary authoritarian regimes in Asia? Coming at a critical time, and one of growing interest in this Southeast Asian country among researchers and policy-makers, Debating Democratization in Myanmar addresses this complex question from a range of disciplinary and professional perspectives. Chapters by leading international scholars and practitioners, activists and politicians from Myanmar and around the world cover political and economic updates, as well as the problems of democratization; the re-engagement of democratic activists and exiles in domestic affairs; the new parliament, the electoral system, and everyday politics; prospects for the economy; ethnic cooperation, contestation and conflict; the role of the army and police forces; and conditions for women. Together they constitute an empirically deep and analytically rich source of readable and relevant material for anyone keen to obtain a greater understanding of what is happening in Myanmar today, and why.